Speech quality for LPC envelope criterion - Shah, Asadullah; Shah, Zoya (IIUM Press, 2011)
The design of STOM based upon LPC envelope distance is used in simulation. The simulation based upon this criterion, performance of the SIDM is provided in this chapter. The quality of speech is measured subjectively